Is there an influence of routine daily transcranial doppler examination on clinical outcome in patients after aneurysmal subarachnoid hemorrhage? - Ehrlich, Gregory Marius; Kirschning, Thomas; Wenz, Holger; Hegewald, Aldemar Andres; Groden, Christoph; Schmiedek, Peter; Scharf, Johann; Seiz-Rosenhagen, Marcel (World neurosurgery, 2016)
Background - Transcranial Doppler (TCD) is widely used as a daily routine method to detect vasospasm in patients after aneurysmal subarachnoid hemorrhage (aSAH); however, there are only limited data about the real benefit of this examination. Therefore, the clinical outcome of 2 cohorts with and without daily TCD after aSAH was assessed. - Methods - All patients included in this study received a standardized diagnostic and treatment protocol. Fifty patients admitted with aSAH from January 2013 to December 2013 received daily TCD measurements; 39 patients admitted from January 2014 to September 2014 received no TCD measurements. Data on clinical grade (Hunt and Hess grade), severity of bleeding (Barrow Neurological Institute grade), localization of aneurysm, and angiographic or clinically relevant vasospasm were collected prospectively. The Glasgow Outcome Scale, modified Rankin Scale, and the National Institute of Health Stroke Scale were used as clinical outcome parameters. - Results - Patient baseline characteristics and clinical data were comparable; treatment modality of the aneurysm was not different between the groups (P = 0.7756). No significant difference between the Hunt and Hess grade (P = 0.818) and the Barrow Neurological Institute grade (P = 0.1551) was observed. There was also no significance concerning the incidence of angiographic or clinically relevant vasospasm between both groups (P = 0.5842 and P = 0.7933). Glasgow Outcome Scale, mRS, and National Institute of Health Stroke Scale as the primary outcome parameters showed no significant difference in morbidity and mortality between both groups (mortality P = 0.8544). - Conclusions - With the limitation of an explorative cohort study, the results indicate that routine TCD studies do not improve the overall outcome of patients after aSAH.
Gesehen am 02.04.2019